2015
DOI: 10.1038/bjc.2015.276
|View full text |Cite
|
Sign up to set email alerts
|

Coffee, tea, caffeine intake, and the risk of cancer in the PLCO cohort

Abstract: Background:The association between coffee intake, tea intake and cancer has been extensively studied, but associations are not established for many cancers. Previous studies are not consistent on whether caffeine may be the source of possible associations between coffee and cancer risk.Methods:In the Prostate, Lung, Colorectal, and Ovarian cancer screening trial, of the 97 334 eligible individuals, 10 399 developed cancer. Cancers included were 145 head and neck, 99 oesophageal, 136 stomach, 1137 lung, 1703 br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
104
4
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(115 citation statements)
references
References 43 publications
5
104
4
2
Order By: Relevance
“…21 The null association between coffee consumption and glioma is somewhat surprising given the previously observed inverse associations between coffee intake and other cancers and beneficial effects on cardiometabolic health; however, other studies have revealed that glioma risk factors appear to differ from those for other cancers, such as smoking. 1,3,6,7,10,11,39…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 The null association between coffee consumption and glioma is somewhat surprising given the previously observed inverse associations between coffee intake and other cancers and beneficial effects on cardiometabolic health; however, other studies have revealed that glioma risk factors appear to differ from those for other cancers, such as smoking. 1,3,6,7,10,11,39…”
Section: Discussionmentioning
confidence: 99%
“…Increased consumption of tea and coffee, two of the most popular beverages worldwide, has been associated with decreased risk of cancers of several sites in human studies. [1][2][3][4][5][6][7][8][9][10] Less is known about the association between tea or coffee consumption and risk of glioma, a cancer for which few lifestyle factors have been identified. 11,12 Coffee is a rich source of caffeine, and both tea and coffee contain additional biologically active compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Such changes could lead to non‐differential measurement error in the assessment of coffee consumption, which could bias results toward the null. Diverging findings in different studies might be also owing to the different types of raw coffee and the different concentrations and preparations, as the particle content and dissolved caffeine content may differ . We did not identify a differing association by caffeinated or decaffeinated coffee consumption, similar to HPFS and the Prostate, Lung, Colorectal and Ovarian ( PLCO ) Cancer Screening study cohort, but these and other types of coffee (e.g., type of coffee bean, roasting and brewing methods) should be investigated in greater detail in future studies.…”
Section: Discussionmentioning
confidence: 80%
“…Coffee has been reported to favorably affect inflammation, lung function and insulin sensitivity, and subsequently reduce mortality risk (41). There are some reports about coffee intake and cancer risk, and the results are variable (34)(42-43). Especially, it has been reported that coffee intake may be associated with increased risk of lung cancer.…”
Section: Discussionmentioning
confidence: 99%